2023
DOI: 10.35633/inmateh-70-14
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research on Energy Consumption in the Lamination and Drawing of Dough

Mariana- Gabriela MUNTEANU,
Gheorghe VOICU,
Gabriel-Alexandru CONSTANTIN
et al.

Abstract: This paper presents an analysis of the variation of energy consumption in the lamination and drawing process of bagel doughs. Also, the paper highlights the farinographic characteristics (water absorbtion, dough develpomnet time, dough stability, degree of dough softening and farinographic index) of the floour used for the dough preparation for which the energy consumption during lamination and drawing was determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
2
0
0
Order By: Relevance
“…In our study, we observed a positive correlation between flour bran and flour recovery with grain hardness, along with +ive correlations between flour bran and water absorption. These findings are consistent with earlier studies [24,25], which reported that an increase in bran proportion leads to higher flour protein (%). Furthermore, our investigation confirmed +ive correlations between protein (%) and quality attributes SDS-SV and wet and dry gluten in line with previous research [26,27].…”
Section: Correlation Among Traitssupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, we observed a positive correlation between flour bran and flour recovery with grain hardness, along with +ive correlations between flour bran and water absorption. These findings are consistent with earlier studies [24,25], which reported that an increase in bran proportion leads to higher flour protein (%). Furthermore, our investigation confirmed +ive correlations between protein (%) and quality attributes SDS-SV and wet and dry gluten in line with previous research [26,27].…”
Section: Correlation Among Traitssupporting
confidence: 93%
“…Notably, significant correlations between bread volume and STAB have also been reported [23]. Typical bread flour characteristics include higher water absorption (≥60%), a dough development time of ≥3 min, and STAB of ≥8 min [24]. In our sample set of 65 genotypes, 26.66% of genotypes met at least two of the criteria for bread flour quality, while several genotypes displayed characteristics indicative of soft grain, suggesting decreased tolerance to mixing.…”
Section: Correlation Among Traitssupporting
confidence: 53%